Through superheroes, America spreading religious propaganda - Meyfian, Raka Elda (Journal of Religion and Linguistics, 2024)
This article explores the role of propaganda in shaping religious narratives through the lens of superhero films. Propaganda's ability to frame narratives and influence how individuals interpret historical events is crucial in determining whether an event or history is perceived as good or bad. By selectively highlighting aspects that serve specific agendas, propaganda integrates its messages into our daily lives almost unnoticed. Various mediums, particularly film, serve as effective tools for disseminating propaganda, with superhero films like "Captain America: The First Avenger" (2011) exemplifying how entertainment intertwines with ideological messages. These films offer heroic narratives that entertain audiences while subtly promoting underlying agendas that reflect nationalistic or religious values. The study emphasizes the need for critical engagement with media beyond entertainment, recognizing that films are not just escapism but convey influential ideologies needing scrutiny. By examining the intersection of propaganda and superhero narratives, this article aims to enhance understanding of how media influences our perceptions of history and religion, encouraging a more critical approach to interpreting these narratives.